2004
DOI: 10.1086/383525
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Disk‐dominated Galaxies. II. Color Gradients and Stellar Population Models

Abstract: We investigate optical and near-IR color gradients in a sample of 172 low-inclination galaxies spanning Hubble types S0-Irr. The colors are compared with stellar population synthesis models from which luminosityweighted average ages and metallicities are determined. We explore the effects of different underlying star formation histories and additional bursts of star formation. Our results are robust in a relative sense under the assumption that our galaxies shared a similar underlying star formation history an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
260
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(295 citation statements)
references
References 65 publications
34
260
0
Order By: Relevance
“…These typically have shown color profiles that become bluer with increasing radius (e.g., MacArthur et al 2004). It is only recently that systematic studies of the outer disks have shown the trend toward redder colors that is seen in our deep images.…”
Section: Comparison To Previous Studiesmentioning
confidence: 54%
“…These typically have shown color profiles that become bluer with increasing radius (e.g., MacArthur et al 2004). It is only recently that systematic studies of the outer disks have shown the trend toward redder colors that is seen in our deep images.…”
Section: Comparison To Previous Studiesmentioning
confidence: 54%
“…This limitation not only applies to integrated data, but also to surface brightness profiles and color gradients. For instance, the so-called inside-out scenario for the formation of galactic disks predicts that the timescale of gas infall and conversion into stars increases with radius, leading to radial variations of the star formation history (SFH), which are in turn observationally translated into color gradients (de Jong 1996; Bell & de Jong 2000;MacArthur et al 2004;Taylor et al 2005). Given that the dust content also changes with radius, it is key to properly quantify that variation with direct tracers of dust extinction; otherwise, derived parameters such as the radial growth rate of disks might be biased (see Muñoz-Mateos et al 2007 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…When we can apply these tools to objects at different redshifts, we can see how changes in the spatial distribution of stellar mass in the disks actually take place. Color gradients have been extensively used in the literature as a way to extract information on both ages and metallicities through the galaxy radial profiles in the local universe (e.g., MacArthur et al 2004). However, an interesting point these previous works missed was the connection between the color distribution and the break phenomenology.…”
Section: Introductionmentioning
confidence: 99%